MIR-155 as a potential biomarker for disease severity in st-segment elevation myocardial infarction: insights from a university-affiliated cardiovascular center - Ailyn Morales-Rentería; Amina Ruiz-Santos; Luis M. Amezcua-Castillo; Jazmín A. Guerra-López; Kietseé A. Díaz-Domínguez; José L. Sánchez-Gloria; Héctor Gonzalez-Pacheco; Luis M. Amezcua-Guerra (Revista de Investigación Clínica)
Background: MiR-155 plays a role in inflammatory pathways and cardiovascular diseases, though its relationship with inflammation, atherosclerosis, and outcomes in ST-elevation myocardial infarction (STEMI) is not well established. Objective: To investigate associations between miR-155 levels, inflammation, atherosclerotic burden, and major adverse cardiovascular events (MACE) in STEMI patients. Methods: Sixty-nine STEMI patients and 16 healthy controls were recruited from a specialized university-affiliated cardiovascular center. MiR-155 expression and serum interleukin (IL)-1β, IL-6, and tumor necrosis factor levels were measured. Patients were grouped into tertiles based on miR-155 expression. Clinical data, atherosclerotic burden (through cardiac catheterization), and in-hospital MACE were recorded. Results: MiR-155 levels were significantly lower in STEMI patients compared to controls (median 54.2, vs. 152.8 arbitrary units; p = 0.003). Higher miR-155 tertiles were associated with a greater prevalence of three-vessel occlusion (34% vs. 13% vs. 4%; p = 0.007) and increased incidence of pulmonary edema (13% vs. 0% vs. 0%; p = 0.030). No significant correlation was found between miR-155 and inflammatory or myocardial markers. Conclusion: Dysregulated miR-155 expression in STEMI patients may influence disease severity and MACE risk, independent of inflammation or myocardial damage markers. (REV INVEST CLIN. 2025;77(1):6-12)